2018
DOI: 10.3399/bjgp18x694901
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein: guiding antibiotic prescribing decisions at the point of care

Abstract: ProvenanceCommissioned; not externally peer reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A recent editorial by Cals and Ebell discussed how the CRP test might be incorporated into clinical decision rules by combining the test result with symptoms and findings. 26 Correspondingly, the authors found that older patients and those with a fever, dyspnoea, abnormal lung auscultation, ear/facial pain, and those with a poor general appearance were prescribed antibiotics at lower CRP levels than other patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…A recent editorial by Cals and Ebell discussed how the CRP test might be incorporated into clinical decision rules by combining the test result with symptoms and findings. 26 Correspondingly, the authors found that older patients and those with a fever, dyspnoea, abnormal lung auscultation, ear/facial pain, and those with a poor general appearance were prescribed antibiotics at lower CRP levels than other patients.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, most studies on the use of CRP tests in patients with acute RTIs have been performed in patients with acute cough, and solid evidence is lacking for its use in patients with other infections. 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous biomarkers to identify bacterial infections have been proposed [19], but none have perfect sensitivity and specificity. The most studied is C-reactive protein (CRP), a marker of inflammation that has been in clinical use for decades [20]. While in some populations it has underperformed, particularly at the severe end of the clinical spectrum [21], in many studies CRP has been found to be appropriately sensitive and moderately specific to identify patients with a bacterial infection [22, 23].…”
Section: Introductionmentioning
confidence: 99%